Milkfish Agribusiness Development At Otak-otak And Smoked Milkfish Enterprises Group In Sidoarjo - Mimit Primyastanto; Mohammad Firdaus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT The aim of this community service was to introduce new technology of milk fish to improve its economic value. The activity was conducted by extension and demonstrating to the small scale industry (milkfish gel/otak-otak and smoked milkfish) in Sidoarjo Regency. The success of activities was evaluated by qualitative and quantitative analysis. The results showed that the community was interested to try and implement this new technology (smoking cash fish, meat mincer, and grinder machine). However, there were some problems for the small scale industry to apply this method, such as inadequate equipment. Therefore, such technology was only conducted by home industry that still cannot extend its market share, is the only industry who implemented such technology. As the result, selling activities was cannot operates well. The suggestions from this activity was important to make business partnership between government, entrepreneur and the other institution that has related with this activity to increase society incomes. Keywords: economic value, milk fish, smoking cash fish, meat mincer, grinder machine